Prevalence of intestinal Protozoa infection in Misurata – Libya (Journal of Humanitarian and Applied Sciences, 2023)
The study was carried out within the period of January to June 2018. at Misurata Central laboratory A total of 394 patients attending clinics and admission were recurited for this study the consisted of (185) males and (209) of females. Age group between 1-40 years. The results: out of 394 samples analyzed (209 females, 185 males) in Misurata Central laboratory (2018) : 69(19.77%) stool samples were positive for cysts. The common parasite was Entamobe coli 6.3% followes by Entamobe histolytica 3.2% and Giardia lamblia 0.7%, the response rate of males was 28(7.10%) and 41 cases (10.4%) rate was seen in females (P
Keywords: intestinal protozoa; parasites; pathogenic; Misurata; Preralence